Magnitude and associated factors of postpartum family planning uptake among postpartum women in Ethiopia: an umbrella review - Geltore, Teketel Ermias; Alemu, Simegn; Angelo, Abiy Tadesse; Mamito, Teketel Tesfaye; Orsongo, Workneh Elias; Foto, Lakew Lafebo; Hadaro, Tesfahun Simon (Frontiers in Global Women's Health, 2024)
BackgroundThe World Health Organization indicates that despite advancements, the rates of maternal and neonatal mortality and morbidity during the postpartum period continue to be alarmingly high. Furthermore, untapped opportunities to enhance maternal health and promote effective newborn care, including family planning services, have not been fully leveraged. Earlier meta-analyses and systematic reviews have addressed this subject; however, a thorough evidence synthesis has not been provided. Therefore, the objective of this study was to compile the existing systematic reviews (SRs) concerning postpartum family planning uptake among postpartum women in Ethiopia.MethodThis review used an umbrella review method, incorporating numerous systematic reviews. We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and the Meta-analysis of Observational Studies guideline (MOOSE). A comprehensive literature review was conducted across prominent four electronic databases (including MEDLINE/PubMed, Cochrane, Web of Science and Science Direct) from June 15, to July 15, 2024. This review encompassed investigations carried out within the uptake of family planning among post-partum women and its determinants in Ethiopia were the primary outcome. A set of inclusion criteria was established to identify all pertinent systematic reviews, including studies, with no restrictions on data collection and publication year. The quality of the methods was evaluated using the Assessment of Multiple Systematic Reviews tool, (AMSTAR) tool. Statistical analysis was conducted using STATA version 17 software, and the 95% confidence interval was utilized to establish statistical significance. I-squared statistics were employed to evaluate the heterogeneity of the studies by using a random-effects meta-analysis model.ResultsThe umbrella review includes five studies with a total of 44,276 postpartum women. The pooled prevalence of postpartum family planning utilization was 36.41% (95% CI: 24.78, 48.03). Family planning counseling (AOR: 4.12, 95% CI: 2.89, 4.71), couple discussion (AOR: 3.06, 95% CI: 1.42, 5.60), and postnatal follow-up (AOR: 3.48, 95% CI: 2.60, 4.83) were significantly associated with postpartum family planning uptake.ConclusionThe study results indicate that the adoption of postpartum family planning in Ethiopia requires focused intervention. This can be achieved by identifying and enhancing community frameworks to involve men in reproductive health initiatives and by providing comprehensive family planning information and services during postnatal care. Addressing the aforementioned factors is crucial to mitigate the risks associated with unintended pregnancies and to manage the swift increase in population.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024568435, PROSPERO (CRD42024568435).